Pengaruh Gambar Dan Video Terhadap Hasil Belajar Bahasa Indonesia Pada Materi Unsur Intrinsik Puisi SMA Di Pontianak - Sari’ani Sari’ani; Haratua Tiur Maria S; Venny Karolina (Journal on Education, 2023)
This research aims to evaluate the influence of the use of learning media, especially image and video media, on student learning outcomes in class X SMAN 12 Pontianak in Indonesian language subjects with the intrinsic elements of poetry. By using experimental methods and data analysis using SPSS. The results showed that there was no significant difference in learning outcomes between the group that used image media and the group that used video. These results have important implications in the development of learning media in the context of language education, showing that this media has an equivalent impact in increasing students' understanding of the intrinsic elements of poetry. These findings provide valuable guidance for the development of more effective and engaging learning strategies in the era of digital education.